The Association Between Obesity and Gerd: A Review of The Epidemiological Evidence - Ali, Zuhaib; Hashmi, Asfia; Gupta, Deepak (Journal of Neonatal Surgery, 2025)
Background: Gastroesophageal reflux disease (GERD) and obesity have both reached epidemic proportions globally, with mounting evidence suggesting a strong association between these conditions. Objective: To systematically review and synthesize epidemiological evidence examining the relationship between obesity and GERD, including its complications such as erosive esophagitis, Barrett's esophagus, and esophageal adenocarcinoma. Methods: A comprehensive review of epidemiological studies, meta-analyses, and systematic reviews was conducted, focusing on population-based studies, cohort studies, and case-control studies that examined the association between various measures of obesity and GERD-related outcomes. Results: Strong epidemiological evidence demonstrates a consistent positive association between obesity and GERD. Meta-analyses show that overweight individuals (BMI 25-30 kg/m²) have a 1.4-1.6-fold increased risk of GERD symptoms, while obese individuals (BMI ≥30 kg/m²) have a 1.9-2.9-fold increased risk. The relationship exhibits a clear dose-response pattern, with risk increasing progressively across BMI categories, even within the normal weight range. Abdominal obesity, particularly visceral fat accumulation, appears to be a stronger predictor of GERD complications than overall BMI. Weight loss interventions consistently demonstrate improvement in GERD symptoms, with structured programs achieving complete symptom resolution in 65% of participants. Conclusions: The epidemiological evidence overwhelmingly supports a causal relationship between obesity and GERD. The association is consistent across diverse populations, demonstrates biological plausibility through multiple mechanisms, and shows reversibility with weight loss interventions.